Cluster Preface: Perspectives on Organoheteroatom and Organometallic Chemistry - Jiang, Xuefeng (Synlett, 2021)
Xuefeng Jiang is a professor at East China Normal University. He received his B.S. degree in 2003 from Northwest University (China). He then joined Professor Shengming Ma’s research group at the Shanghai Institute of Organic Chemistry (SIOC), Chinese Academy of Sciences, where he received his Ph.D. degree in 2008. From 2008 to 2011, Xuefeng worked as a postdoctoral researcher on the total synthesis of natural products in the research group of Professor K. C. Nicolaou at The Scripps Research Institute (TSRI). His independent research interests have focused on green organosulfur chemistry and methodology-oriented total synthesis.